Early nineteenth-century Hindi/Urdu/Hindustani translations and the politics of emerging linguistic categories. Issue 2 (4th May 2021) - Yadav, Manoj Kumar
ABSTRACT: This article focuses on the translations produced at or prescribed by Fort William College (FWC) in the early nineteenth-century for the study of Hindustani/Urdu/Hindi. It demonstrates that the study of translations in the context of the formation of "new" languages adds fresh insights to our present understanding of Hindi/Urdu and their relationship to other varieties such as Awadhi and Braj. It explores the political context which undergirds the foundation of educational institutions such as FWC in early colonial India and the translation practices endorsed at these institutions for the study of languages and the conceptualization of different linguistic categories. It is hypothesized that within the multilingual context of early nineteenth-century north India, translation played an important role in the formation of new linguistic categories, hierarchies and language boundaries.